2017
DOI: 10.1002/chem.201702662
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Sulfur Functional Groups as Definers of the Chirality at the Metal in Ir and Rh Half‐Sandwich Complexes: A Combined CD/X‐ray Study

Abstract: Mesoionic carbenes (MICs) derived from triazolium salts that contain chiral sulfoxide or sulfoximine functional groups were used to construct enantiopure chiral-at-metal Ir and Rh half-sandwich complexes through the synthetic sequence of MIC complexation/C-H aromatic activation. The process was efficient and diastereoselective for the formation of enantiopure five-membered metallacycles. The use of the enantiomers of the chiral sulfur groups allowed us to prepare complexes that had opposite configurations at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…This strong negative Cotton absorption is maintained (287.0 nm) for the Ir(III) complex 7c. [19] In previous studies, [10] this negative Cotton absorption was assigned to an absolute configuration R at the metallic center. Since absolute configuration R at the Ir(III) for 7b has been unambiguously established by X-ray analysis (absolute structure factor x = 0.013 7), we can conclude that the absolute configuration at the metallic center for complexes 7a and 7c may be R as well.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This strong negative Cotton absorption is maintained (287.0 nm) for the Ir(III) complex 7c. [19] In previous studies, [10] this negative Cotton absorption was assigned to an absolute configuration R at the metallic center. Since absolute configuration R at the Ir(III) for 7b has been unambiguously established by X-ray analysis (absolute structure factor x = 0.013 7), we can conclude that the absolute configuration at the metallic center for complexes 7a and 7c may be R as well.…”
Section: Introductionmentioning
confidence: 93%
“…During our work in the synthesis of transition metal complexes having 1,2,3-triazolylidene (MIC) ligands with enantiopure sulfoxide and sulfoxiimine moieties, [8] we have reported the role of the chiral mesoionic carbene ligand (MIC) in defining the catalytic reactivity of their Au(I) derivatives, [9] preparing enantiopure chiral-at-metal complexes, [10] and enantiopure complexes having chiral-at-metal and chiral planar metallocene moieties. [11] On the other hand, our work in push-pull systems containing a Cr(0) and W(0) Fischer metal carbene moiety, I, clearly demonstrated that the system geometry is reflected in the deactivation of the fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing our work on the use of 1,2,3‐triazolylidene mesoionic carbenes (MICs) containing enantiopure sulfoxide moieties, we reported for the first time the use of these MICs for the preparation of enantiopure cyclometalated Ir III and Rh III half‐sandwich complexes . The process takes place through the sequence MIC coordination/enantioselective C−H activation (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The process takes place through the sequence MIC coordination/enantioselective C−H activation (Scheme ). Metalation to form five‐membered metallacycles produces enantiomerically pure complexes, whereas the formation of the six‐membered analogues is not totally diastereoselective …”
Section: Introductionmentioning
confidence: 99%